Young Children Pause on Phrase Boundaries in Self-Paced Music Listening: The Role of Harmonic Cues. - Kragness, Haley E.; Trainor, Laurel J. (Developmental Psychology, 2018)
Proper segmentation of auditory streams is essential for understanding music. Many cues, including meter, melodic contour, and harmony, influence adults' perception of musical phrase boundaries. To date, no studies have examined young children's musical grouping in a production task. We used a musical self-pacing method to investigate (1) whether dwell times index young children's musical phrase grouping and, if so, (2) whether children dwell longer on phrase boundaries defined by harmonic cues specifically. In Experiment 1, we asked 3-year-old children to self-pace through chord progressions from Bach chorales (sequences in which metrical, harmonic, and melodic contour grouping cues aligned) by pressing a computer key to present each chord in the sequence. Participants dwelled longer on chords in the 8th position, which corresponded to phrase endings. In Experiment 2, we tested 3-, 4-, and 7-year-old children's sensitivity to harmonic cues to phrase grouping when metrical regularity cues and melodic contour cues were misaligned with the harmonic phrase boundaries. In this case, 7 and 4 year olds but not 3 year olds dwelled longer on harmonic phrase boundaries, suggesting that the influence of harmonic cues on phrase boundary perception develops substantially between 3 and 4 years of age in Western children. Overall, we show that the musical dwell time method is child-friendly and can be used to investigate various aspects of young children's musical understanding, including phrase grouping and harmonic knowledge.